Mercury rising [videorecording (DVD)] - Becker, Harold; Willis, Bruce, 1955-; Baldwin, Alec, 1958-; Hughes, Miko, 1986-; Pearson, Ryne Douglas (Universal Home Video, 1999)
Bruce Willis is an outcast FBI agent who is assigned to protect a 9 year old idiot savant who is the target for assassins after cracking a top secret government code.